Derrida, the Scene of Archiving, and the Unhappy Consciousness - Brothman, Brien (Archivaria)

(untitled) (Association of Canadian Archivists, 2025)
What does the philosophy of Jacques Derrida (1930–2004) have to do with the archival community’s recent turn to critical theory? This article proposes that Derrida’s philosophy worked at critical theory’s edges. His much-commented Archive Fever exemplifies Derrida’s longstanding personal and political (post-colonial) critique of the concepts of shelter, home, and belonging and with the presumptions of social, linguistic, and territorial sovereignty. These preoccupations underlie Derrida’s diagnosis of a fever – of an unhappiness or malaise – at the scene of writing/archiving.